Enhancing Self-Directed Learning Skills via Blended Problem-based Learning in Chemistry Learning - Ibrahim, Mohd Mokhzani; Jamaludin, Khairul Azhar; Rosli, Mohd Shafie; Damanhuri, Muhd Ibrahim Muhamad; Taha, Hafsah; Borhan, Mohamad Termizi (CENTRAL ASIA AND THE CAUCASUS, 2022)
Students' mastery of the Three Representation Levels of Chemistry Concept (macroscopic, microscopic, and symbolic) is still weak and this has affected their academic performance in Chemistry subject. This has resulted from the poor engagement of students in the teaching and learning process. The current teaching practice is teacher- centered learning and does not encourage self-directed learning. Therefore, there is a need to implement Blended Problem-Based Learning (BPBL) which encourages students’ self-directed learning in face-to-face and online learning mode. This study is aimed at: (i) identifying how self-directed learning skills are being applied in the BPBL, and (ii) identifying how BPBL enhances Chemistry learning. This study employed a qualitative approach through a case study research design (exploratory and explanatory). Two teachers and 20 students were selected using purposive sampling, which became the sample for this study. Data were collected from observations, students’ documents, and semi-structured interviews and analysed thematically. Generally, the findings indicated that the BPBL approach was able to enhance students’ ability to: (i) plan a problem-solving process, (ii) analyze, assess understanding and provide justification as well as (iii) evaluate references and information. These skills have contributed to mastery of the Three Representation Levels of Chemistry Concept and they were able to avoid the formation of alternative concepts. The findings of this study can serve as a reference to effectively implement BPBL in the context of Chemistry learning in Malaysia.